Adaptive tracking of nonlinear time-delay systems subject to symmetrical dead-zone input - Cao, Zhenxing; Jia, Xianglei; Shao, Yiming; Li, Shuo (Chinese Control Conference, 2020)
This paper investigates the problem of global adaptive tracking by output feedback, for a class of uncertain nonlinear systems with symmetric dead-zone nonlinearity and unknown time-delay in the actuator. In the case that only system output can be measured, we propose a universal adaptive output feedback controller by designing the extended high-gain observer with an adjustable parameter. Then, the stability analysis is performed concisely by using the idea of non-separation principle and high-gain scaling approach instead of backstepping method. In particular, all design parameters are easy to obtain by solving a system of inequalities. Finally, a simulation example is given to illustrate the effectiveness of the proposed controller.